2019
DOI: 10.1016/j.marpolbul.2018.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of port baseline surveys (PBS) in the Adriatic Sea

Abstract: Port baseline surveys (PBS) provide species inventories in and around ports, with a focus on non-indigenous species that may have been introduced by vessels, primarily via ballast water. PBS are an essential tool to support effective management strategies for non-indigenous as well as native harmful aquatic organisms and pathogens (HAOP). This paper describes the methodology of PBS that were conducted in 12 Adriatic ports. The PBS employed existing protocols that were adapted to meet the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Global initiatives have been initiated to standardize sampling for PBBS (Awad, Haag, Anil, & Abdulla, ; HELCOM/OSPAR, ; Kraus et al, ) and are based on morphological taxonomic identification of the species found. Yet, this method lacks accuracy for identification of larvae and eggs, developmental stages at which many NIS are transported (Gittenberger, Rensing, Niemantsverdriet, Schrieken, & Stegenga, ), and relies on taxonomists who are often specialized on the local biota, but who have limited knowledge of alien taxa (Pyšek et al, ) and/or on specific taxonomic groups coexisting in a port (Bishop & Hutchings, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global initiatives have been initiated to standardize sampling for PBBS (Awad, Haag, Anil, & Abdulla, ; HELCOM/OSPAR, ; Kraus et al, ) and are based on morphological taxonomic identification of the species found. Yet, this method lacks accuracy for identification of larvae and eggs, developmental stages at which many NIS are transported (Gittenberger, Rensing, Niemantsverdriet, Schrieken, & Stegenga, ), and relies on taxonomists who are often specialized on the local biota, but who have limited knowledge of alien taxa (Pyšek et al, ) and/or on specific taxonomic groups coexisting in a port (Bishop & Hutchings, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of these legal frameworks is the International Convention for the Control and Management of Ships' Ballast Water and Sediments (IMO, ), which requires that ships treat their ballast water before its release to port, unless they show that the risk of transferring NIS between the donor and recipient ports is limited (David, Gollasch, & Pavliha, ). Such risk assessment requires cataloging biodiversity through port biological baseline surveys (PBBS), which requires collecting samples using various methods (Kraus et al, ) and at different spatial and temporal scales (Lehtiniemi et al, ) given the diverse range of habitats (such as soft sediment, water column, or exposed and sheltered artificial structures) allowing presence of distinct organismal groups (such as benthic macrofauna, fouling organisms, or planktonic organisms).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, monitoring programmes that aim at capturing NIS must be carefully evaluated, as surveys are often restricted to harbours and marinas (e.g. Rohde et al 2017;Kraus et al 2019). We argue that potential overestimations of local oyster populations can be avoided by a multipleexposure sampling approach.…”
Section: Length Frequency Distributionsmentioning
confidence: 99%
“…Depending on protocols guidelines, PBBS can: i) provide a valuable detection system for target species, facilitating species eradication before their proliferation and spread; ii) provide a baseline of native and NIS biodiversity to identify future new introductions; iii) help investigate invasion patterns in relation to abiotic and biotic factors; and iv) provide information on the effects of invasions (Bishop and Hutchings, 2011). One of the papers of this special issue, Strategy of port baseline surveys (PBS) in the Adriatic Sea (Kraus et al, 2019a), includes an overview of existing surveys protocols which provide valuable support to decision-making and to design effective NIS monitoring with conversed pros and cons. Furthermore, this paper offers guidelines for the selection of ports, survey areas, and sampling sites; the scope of parameters, i.e.…”
Section: Figmentioning
confidence: 99%